2011
DOI: 10.1097/cji.0b013e318210ed0e
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Vaccine-induced Primary and Memory CD8+ T-cell Responses by Soluble PD-1

Abstract: Programmed death 1 (PD-1) signaling through its ligands, PD-L1 and PD-L2, has been known to negatively regulate T-cell responses. In addition, PD-L1 has been shown to interact with B7-1 costimulatory molecule to inhibit T-cell responses. Extensive studies have shown that PD-1/PD-L blockade restores exhausted T cells during chronic viral infections and tumors. In this study, we evaluated the effects of soluble PD-1 (sPD-1) as a blockade of PD-1 and PD-L1 on vaccine-elicited antigen-specific T-cell responses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 0 publications
4
89
0
5
Order By: Relevance
“…Any imbalances in this regulatory mechanism may dysregulate the immune responses. The expression of sPD-1 is known to inhibit PD-L1 in various cell types in mice (23,25), including molecules expressing PD-L1 as a result of a CE infection and PD-L1 molecules associated with T cell apoptosis, thereby increasing the secretion of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Any imbalances in this regulatory mechanism may dysregulate the immune responses. The expression of sPD-1 is known to inhibit PD-L1 in various cell types in mice (23,25), including molecules expressing PD-L1 as a result of a CE infection and PD-L1 molecules associated with T cell apoptosis, thereby increasing the secretion of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown that a PD-1/PD-L1 blockade restores exhausted T cells during chronic viral infections and in tumors (28,55). Song et al evaluated the effects of soluble PD-1 (sPD-1) as a blockade of PD-1 and PD-L1 on vaccine-elicited antigen-specific T-cell responses in mice (56). Coadministration of sPD-1 with an Ad-based vaccine could increase antigen-specific CD8 ϩ T-cell responses, indicating a vaccine type-independent adjuvant effect of sPD-1.…”
Section: Discussionmentioning
confidence: 99%
“…PPP2R5C is implicated in the negative control of cell growth and division (54,57). ATF2 and ATF4 have proapoptotic activity and are involved in the upregulation of Fas and FasL (56). PTEN is known to inhibit AKT phosphorylation, involved in phosphorylation of FOXO3a in different cell models (58) as well as it negatively regulates the activation of NF-B and I kinase ␤ (IKK␤) (59).…”
Section: Discussionmentioning
confidence: 99%
“…8183 Emphasizing co-stimulatory molecules, blockage of the receptors through expression of inhibitors or siRNA can assist in the regulation of immune responses that are present during chronic viral infection and cancer. 84, 85 In summary, the diversity and specificity of molecular adjuvants holds enormous potential and will likely continue to receive significant attention on the basis of encouraging preliminary results reported in the clinic.…”
Section: Enhancing Immune Potency Of Dna Vaccinesmentioning
confidence: 99%